Prevalence of drug administration without the guidance of the Veterinarian in companion animals in the City of Areia – PB (Research, Society and Development, 2021)
Companion animals have been treated as family members, they are used to the home environment, being raised as human beings, and therefore an affective bond was created between guardian and animal. For this reason, they are subject to medication without a prescription from a qualified professional, as this is a common practice of humans. Many tutors are unaware of the toxic potential that some drugs have if administered in wrong doses. Incorrect dosage of a drug can lead to an inaccurate diagnosis of serious diseases, chronic problems such as kidney and liver failure, and especially poisoning. Therefore, the objective of this research was to evaluate the prevalence of medication administration cases without the guindace of the veterinarian, in pets, in the city of Areia – PB, Brazil, as well as identify which are the most used drugs and the knowledge of the population about the risks of selfmedication and the toxic potential that some drugs present. 46 online questionnaires were applied through Google Forms® software and 8 face-to-face questionnaires with animal tutors, living in the city of Areia – PB, Brazil, from August to September 2019, totaling 54 questionnaires. The analysis was performed based on the responses of participants who met the inclusion criteria. Although a large part of the interviewees are aware of the risks of self-medication, a high proportion of these people still carry out this practice. The results confirm the need for more clarification to the population and laws in defense of animal health.